Reproductive Women’s Knowledge on Possibility of Pregnancy after Birth but before Resumption of Menstruation and Its Associated Factors in Ethiopia: A Population-Based Study Using the 2016 Ethiopian Demographic Health Survey - Aragie, Teshome Gebremeskel; Gedion, Girma Seyoum (International Journal of Reproductive Medicine, 2022)
Introduction. Worldwide, specifically in developing countries, women believe that a woman cannot become pregnant unless she sees her first postpartum menstruation. Due to this knowledge gap, most women did not use any contraceptives till their 1st postpartum menstruation. Hence, about 44% of women were susceptible to unintended pregnancy in the postpartum period. Assessing women knowledge on possibility of pregnancy after giving birth but before returning of menses and its associated factors will help to increase women’s recognition on the issue and for early commencement of appropriate postpartum family planning methods to reduce burden of unintended pregnancy. Objective. To assess the level of knowledge on possibility of pregnancy after giving birth but before returning of menses and its associated factors among reproductive women in Ethiopia. Methods. A secondary data analysis using the 2016 Ethiopian Demographic Health Survey was employed. Samples were selected using two-stage stratified sampling technique. Descriptive statistics and logistic regressions were used. Adjusted odds ratio (AOR) with 95% confidence interval was used to interpret associations, and a significant association was declared at a p value of <0.05. Result. A total of 15,683 reproductive women aged from 15 to 49 years were included. Of them, about 53% did not know that a woman can get pregnant after giving birth but before resumption of her menstruation. Age being 35 years and above (AOR=1.50; 95%CI=1.34, 1.67), educational status of secondary and above (AOR=1.18; 95%CI=1.06, 1.32), being ever married (AOR=1.67; 95%CI=1.47, 1.89), knowledge of any family planning method (AOR=1.81; 95%CI=1.52, 2.16), getting counseling on family planning methods (AOR=1.41; 95%CI=1.28, 1.55), and being knowledgeable on their ovulatory cycle (AOR=1.68; 95%CI=1.55, 1.82) were found to be significantly associated with being knowledgeable on the issue. Conclusion. Reproductive women’s level of knowledge on the possibility of pregnancy after giving birth but before returning of menses was low. Factors associated with being knowledgeable on the issue were identified. Therefore, strategies should be developed to increase their level of knowledge for reducing unintended pregnancy and its complications by integrating family planning counseling with infant immunization services.